Analysis of stromal mucin in oral epithelial dysplasia & oral squamous cell carcinoma- A histochemical study - Ankita Sahni; Shweta Rehani; Priyanka Kardam; Sneha Sethi; Rashmi Kumari; Yulia Mathias (Journal of Oral Biology and Craniofacial Research, 2019)
Background: Mucins are glycoproteins that act as a selective molecular barrier and its alterations usually accompany the carcinogenesis. Aim: To evaluate the transition of mucins in the grades of oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC) using histochemical stains. Materials & Method: A total of 66 samples of variable grades of OED and OSCC and each section was stained with PAS, Alcian blue- PAS (AB-PAS) and Aldehyde fuschin – Alcian blue (AF-AB). Mucins pattern and intensity were examined at 5 randomly selected fields on 10x magnification. Results: 1. PAS stain – Predominantly OED and OSCC showed a diffuse pattern with a gradual decrease in intensity in OED and overall a weak intensity in OSCC. 2. AB-PAS stain – Neutral mucins showed gradual increase in its intensity in grades of OED and OSCC with no predominant pattern. The intensity for the acid mucins remains weak in all the grades of OED and OSCC with diffuse distribution, except in higher grades of OED and OSCC. 3. AF- AB stain - For sulphated mucins, in OED a focal and diffuse pattern was observed in OSCC with minimal intensity. The carboxylated mucin was absent in both. Conclusion: Mucins undergo change in its pattern and intensity in varying grades of OED/OSCC. Although in GIT and other mucosa, the expression of altered mucin is a recognized factor, seldom research has been done in OED and OSCC. Thus, the present study could be the stepping stone in the exploration of mucinous alteration in OED and OSCC.